Effect of harvesting time on seed physiological quality, chemical composition and storability of soybeans (Scientia Agricola, 1994)
Soybeans IAC-8 were harvested in the growth stages R7 and R8 commercial harvesting time and at two other subsequent times to compare their physiological and technological characteristics. Seeds were stored at two moisture levels, 12% and 15%, for 6 months. Germination and vigor (acelerated aging, electrical conductivity), oil and free fatty acids, peroxide and iodine values were evaluated periodically. As expected, the time of harvesting and seed moisture content affected seed performance, while oil content did not correlate to physiological quality as did acidity, peroxide value and iodine number.